A novel numerical model for the interaction between the solidification front of a semicrystalline polymer and spherical particles. Issue 3 (26th October 2018) - Agaliotis, Eliana; Vazquez, Analia; Bernal, Celina
Abstract: The interaction between a solidification front of a semicrystalline polymer and a spherical particle is a topic of main interest because it addresses particle dispersion/distribution and materials behavior associated with this issue. In this paper, this interaction is investigated from numerical analyses by a computational fluid dynamics model that employs the shape of the interface to calculate drag and repulsion forces. The results obtained in turn are used to determine the conditions under which the particle is dragged by the solidification front. This is employed then to predict critical solidification front velocities for pushing as a function of particle size. The results shows that the numerical model developed here is able to accurately predict the conditions for particle pushing in semicrystalline polymers. The required cooling conditions which lead to a redistribution of the particles below 50 µm of radius during solidification in polymer composites and blends can be determined with the proposed model. Abstract : The present report addresses particle dispersion/distribution in semicrystalline polymers by the development of a numerical model. Polymeric blends and composites, especially thermoplastic composites, are attractive materials. The employed of a numerical model to determine the required cooling conditions which lead to a redistribution of particles during solidification in polymer composites and blends is topic of main interest because it addresses particle dispersion and the materials behavior associated with this issue.